Assembly of Rolling Circle Amplification‐Produced Ultralong Single‐Stranded DNA to Construct Biofunctional DNA Materials. Issue 9 (15th December 2022) - Tang, Jianpu; Liang, Aiqi; Yao, Chi; Yang, Dayong
Abstract: The Review by Yang, Yao and colleagues (DOI: 10.1002/chem.202202673 ) describes recent developments in biofunctional DNA hydrogels and DNA nanocomplexes based on rolling circle amplification (RCA) and introduces assembly strategies and functionalization methods of the ultralong single‐strand DNA produced by RCA to construct biofunctional materials. Abstract : DNA materials have attracted considerable attention in biomedical applications due to their predictable structure and designable functions. Recently, various biofunctional DNA materials have been developed through rolling circle amplification (RCA). Herein, the assembly strategies to construct RCA‐based DNA material in recent years are summarized in two main parts, including the construction of DNA hydrogel and DNA nanocomplex.